Current and emerging treatment options in the management of Friedreich ataxia - Michelangelo Mancuso (Dove Medical Press, 2010)
Michelangelo Mancuso, Daniele Orsucci, Anna Choub, Gabriele SicilianoDepartment of Neuroscience, Neurological Clinic, University of Pisa, Pisa, ItalyAbstract: Friedreich ataxia (FRDA) is the most common autosomal recessive ataxia. Oxidative damage within the mitochondria seems to have a key role in the disease phenotype. Therefore, FRDA treatment options have been mostly directed at antioxidant protection against mitochondrial damage. Available evidence seems to suggest that patients with FRDA should be treated with idebenone, because it is well tolerated and may reduce cardiac hypertrophy and, at higher doses, also improve neurological function, but large controlled clinical trials are still needed. Alternatively, gene-based strategies for the treatment of FRDA may involve the development of small-molecules increasing frataxin gene transcription. Animal and human studies are strongly needed to assess whether any of the potential new treatment strategies, such as iron-chelating therapies or treatment with erythropoietin or histone deacetylase inhibitors and other gene-based strategies, may translate into an effective therapy for this devastating disorder. In this review, we try to provide an answer to some questions related to current and emerging treatment options in the management of FRDA.Keywords: frataxin, idebenone, oxidative stress